THE IMPACT AND DIFFERENCES OF ANTHROPOMETRIC CHARACTERISTICS AND MOTOR SKILLS IN TWO GENERATION STUDENTS IN THE ATHLETIC DISCIPLINE – RUNNING 1500m. - Simeonov, Aleksandar; Ratko Pavlović; Jana Karshakovska-Dimitrioska (Faculty of Physical Education, Sport and Health, Skopje, 2022)
Anthropometric characteristic and motor skills, are very important in the result of the athletic discipline – 1500m. The aim of this research was to determine the impact and differences in morphological characteristics and motor skills in athletic discipline 1500m., at both generations of students at the Faculty of Physical Education, Sports and Health. In a sample of 100 respondents, consisted of full-time second year students at the age of 20 years with ± of 6 months at the Faculty of Physical Education Sport and Health in Skopje. divided into two groups 50 respondents in both generations surveyed - 2016 and 2018, research has been done. Methods: In our research for assessment of the morphological structure of the respondents, 12 morphological variables were used, and 5 motor variables for assessment of psychomotor abilities. The athletic discipline – 1500m. is used as a criterion variable. Results: From the obtained results of the regression analysis, we noticed that the morphological variables have a significant impact on the criterion variable - 1500m. only in the first group of participants - 2016 generation (Q=.007). Regarding the motor skills that were the subject of analysis in our research, we found that all five motor variables used as a test to test their abilities have a significant impact as a system on the criterion variable – 1500m. (Q=.000). According to the multivariate (MANOVA) and univariate analysis (ANOVA) of the results of both groups of entities, we noticed that both groups of respondents differ in their morphological characteristics and biomotor abilities (Q=.000). Conclusion: Based on the results obtained from the applied research procedure, we came to the conclusion that the morphological structure of the respondents has a significant role in achieving greater heigth in аthletic discipline – 1500m.. In terms of motor skills, we came to the conclusion that students should use the motor tests that were used in the research in the preparation phase, in order to be able to successfully meet the norm and achieve better results in the discipline – 1500m. The differences between the respondents would be smaller if they pay more attention to the preparation for the fulfillment of the norm in this athletic discipline.
Keywords: morphology; motor skills; 1500m.; analysis; impact; differences